PERUBAHAN PERILAKU KOMUNIKASI KAUM PEREMPUAN PENGGUNA INSTAGRAM STORIES DI KOTA MAKASSAR - Erniwati Erniwati; Muh. Resa Yuldianto Suldani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2020)
The development of internet-based communication technology has brought changes to the communication behavior of the digital society. Changes in communication in the digital era have an impact on the form of messages that previously used writing or texting through online chat services on social media to become audio-visual or video messages. This development is in line with the widespread use of social media in the digital community, especially women. One of the social media that is becoming a trend today is Instagram with the Instagram Stories feature as a feature that provides new things in communicating in the community. Based on this phenomenon, this study aims to determine how Instagram Stories brings changes in communication behavior among women in the city of Makassar. The research method used is a qualitative descriptive approach where the researcher makes observations through an analysis of the communication behavior of Instagram story users and is supported by the results of interviews with informants. The results of the study then showed that the Instasgram story service gave changes to the communication behavior of Instagram users which had an impact on the user's social life. Changes in communication behavior occur because they are supported by interesting information obtained from uploading photos and videos of users on Instastory.